Cytogenetic Identification and Molecular Marker Analysis of Two Wheat–Thinopyrum ponticum Translocations with Stripe Rust Resistance - Guotang Yang; Yi Han; Huihui Yin; Xingfeng Li; Honggang Wang; Yinguang Bao (Plants)
Stripe rust, induced by Puccinia striiformis f. sp. tritici (Pst), is one of the most destructive fungal diseases of wheat worldwide. Thinopyrum ponticum, a significant wild relative for wheat improvement, exhibits innate immunity to this disease. To transfer the stripe rust resistance gene from Th. ponticum to wheat, two translocation lines, SN21171 and SN52684, were produced through distant hybridization techniques. Disease evaluation results showed that these two lines were immune to Pst species CYR32 at the adult plant stage. Molecular cytogenetic analyses and specific intron-targeting markers amplification results revealed that SN21171 and SN52684 harbor several T3Eb-3DS·3DL and T1Eb-1BS·1BL translocation chromosomes. Furthermore, the comparison of the chromosome karyotype from two translocation lines and their recurrent parent YN15, revealed that structural variation occurred in chromosomes 2A, 5A, 2B, 4B, 5B, and 6B in SN21171 and chromosomes 5A, 3B, 4B, 5B, 6B, and 7B in SN52684. Agronomic trait assessments uncovered advantageous properties in both lines, with SN21171 matching the recurrent parent and SN52684 exhibiting elevated higher grain number per main spike and increased thousand grain weight. These two translocation lines and specific markers may apply to wheat stripe rust-resistance breeding.